Breeding biology of Spectacled Tyrant (Hymenops perspicillatus) in the southeastern Pampas region, Argentina - Pretelli, Matías Guillermo (2013)
The Spectacled Tyrant (Hymenops perspicillatus) is a flycatcher that inhabits open lands, grassy areas near water bodies, marshes, fields and pastures in southern South America. Our aim was to describe the breeding biology of Spectacled Tyrants in native tall grasslands, specifically by studying their reproductive phenology and breeding success. The study was developed in the southeastern Pampas region, Argentina. We conducted nest searching and monitoring during the 2010–2011 and 2011–2012 breeding seasons. We found 88 nests. The breeding season was from mid-October to late January. Clutch size was 2–3 eggs, mode 5 2. Incubation and nestling periods were 15.8 6 0.7 days and 14.7 6 0.6 days, respectively. Nest predation was higher during the incubation period than during laying and nestling periods. The probability of nest success from egg-laying to fledging was 0.24. This species shows life-history traits in accordance with other South American temperate birds.